2005
DOI: 10.1523/jneurosci.0433-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Orbital and Medial Prefrontal Cortex by Methylphenidate in Cocaine-Addicted Subjects But Not in Controls: Relevance to Addiction

Abstract: Drugs of abuse are rewarding to addicted and nonaddicted subjects, but they trigger craving and compulsive intake only in addicted subjects. Here, we used positron emission tomography (PET) and [18 F]deoxyglucose to compare the brain metabolic responses (marker of brain function) of cocaine-addicted subjects (n ϭ 21) and controls (n ϭ 15) to identify brain regions that are uniquely activated in addicted subjects by intravenous methylphenidate (a drug that cocaine-addicted subjects report to be similar to cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
193
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(207 citation statements)
references
References 73 publications
8
193
1
5
Order By: Relevance
“…In contrast to decreased basal metabolic function, neuroimaging studies in psychostimulant dependent subjects have consistently reported that upon exposure to drug-related cues or low doses of psychostimulants, metabolic activity increases in the anterior cingulate, dorsolateral prefrontal cortex (PFC), and NAc (Bonson et al, 2002;Volkow et al, 2005). Our results showed that GLU efflux increased in both the dmPFC and NAc during cue-induced and meth-primed reinstatement.…”
Section: Increased Glu Efflux During Meth Seekingmentioning
confidence: 44%
“…In contrast to decreased basal metabolic function, neuroimaging studies in psychostimulant dependent subjects have consistently reported that upon exposure to drug-related cues or low doses of psychostimulants, metabolic activity increases in the anterior cingulate, dorsolateral prefrontal cortex (PFC), and NAc (Bonson et al, 2002;Volkow et al, 2005). Our results showed that GLU efflux increased in both the dmPFC and NAc during cue-induced and meth-primed reinstatement.…”
Section: Increased Glu Efflux During Meth Seekingmentioning
confidence: 44%
“…when triggered by stress, drug cues or drug per se, reinstatement constitutes a highly motivated behavior 104 , and is virtually abolished by lesions in ventral tegmental area 105 or dopamine antagonist infusion into dorsal striatum 106 . Additionally, human functional neuroimaging data suggest that the intense desire that motivates drug seeking depends on primary processing of drug-related cues in oFc [107][108][109] .…”
Section: Ventromedial Prefrontal Cortex and Dopamine: Decoding Decisimentioning
confidence: 99%
“…Recent magnetic resonance (MR) imaging studies have provided strong evidence that cocaine abuse is associated with structural brain abnormalities in both gray matter (GM) and white matter (WM) (Bartzokis et al, 2002;Fein et al, 2002;Franklin et al, 2002;Lim et al, 2002;Moeller et al, 2005). Evidence from functional neuroimaging studies and investigations of neuropsychological deficits also point to long-term changes in brain status associated with cocaine abuse (Bolla et al, 2000;Goldstein et al, 2004;Volkow et al, 2005). Fully characterizing the nature of the underlying structural abnormalities in cocaine abusers is critical to understanding the impact of the drug on long-term functioning.…”
Section: Introductionmentioning
confidence: 99%